ADAM: God's beloved - NOUWEN, Henri J. M (Maryknoll, New York Orbis Books, 1997)
Through the story of Adam Nouwen found a new way to tell God's story of Jesus and the story of all of us human creatures, broken and yet beloved, who live in a world charged with the mystery of God's overwhelming love.